Anesthetic Management In Patient With Laparoscopic Cholesistectomy - Zaki Fikran; Anna Millizia; Arief Kresna (Faculty of Medicine University of Malikussaleh, 2022)
Abstract Cholelithiasis is one of the most common diseases. One of the treatments that can be done is a laparoscopic cholecystectomy. This action is one type of minimally invasive procedure that aims to minimize trauma from the process, which aims to minimize trauma from the surgical process but with satisfactory results. Laparoscopy is a minimally invasive surgical procedure by introducing CO2 gas into the peritoneal cavity to create a space between the anterior abdominal wall and the viscera, thereby providing endoscopic access into the peritoneal cavity. Anesthesia induction was performed under general anesthesia with intubation. The procedure was successful and the patient returned to the ward in good condition.